The Impact of the Work Environment and Services on the Degree of Job Satisfaction of Faculty Members A field Study at Nile Valley University – Sudan (2021 – 2022 AD) - Osman, Omer Mustafa Ali (Journal of Economic, Administrative and Legal Sciences, 2023)
The study dealt with the degree of job satisfaction of faculty members at Nile Valley University about the work environment and the services provided to them by the university administration. The study aimed to identify the impact of work environment and services on the degree of job satisfaction of faculty members at Nile Valley University. The study used a questionnaire which distributed to 50 of the study sample, the researcher used the analytical descriptive method. A number of results were reached, the most important of which is. The university administration allows employees sufficient flexibility and job description for each job title, university administration. It allows workers the freedom to express their ideas and suggestions. Based on the results of the study, recommendations were made, the most important of which is that the university administration should provide a suitable place for the nature of work and provide a healthy environment for work. The university administration must provide the opportunity for employees to participate in planning and decision-making.